Self-management program improves participation in patients with neuromuscular disease: A randomized controlled trial. (29th October 2019) - Veenhuizen, Yvonne; Cup, Edith H.C.; Jonker, Marianne A.; Voet, Nicoline B.M.; van Keulen, Bianca J.; Maas, Daphne M.; Heeren, Anita; Groothuis, Jan T.; van Engelen, Baziel G.M.; Geurts, Alexander C.H.
Abstract : Objective: To investigate the effectiveness of Energetic, a self-management group program combining aerobic training, energy conservation management, and relapse prevention to improve social participation in patients with neuromuscular disease (NMD) and chronic fatigue. Methods: In this multicenter, assessor-blinded, 2-armed randomized controlled trial with repeated measurements, 53 patients with various types of NMD and chronic fatigue were randomly allocated to Energetic, a 4-month group intervention, or to usual care. The primary endpoint was social participation assessed with the Canadian Occupational Performance Measure (COPM) performance scale immediately postintervention. Secondary outcomes included COPM satisfaction scale, 6-Minute Walk Test (6MWT), and Checklist Individual Strength–subscale fatigue. Participants were followed for 11 months postintervention. Data were analyzed with linear models that account for repeated measurements. Results: Directly after intervention, the mean group difference for COPM-performance was 1.7 (95% confidence interval [CI] 1.0–2.4; p < 0.0001) in favor of the intervention group (n = 29), adjusted for baseline, sex, diagnosis, and work status. This effect was retained at 11 months follow-up (0.9; 95% CI 0.0–1.7; p = 0.049). The COPM satisfaction scale and 6MWT improved more in the intervention group compared to usual care. After 3 and 11 months follow-up, most beneficial effects on social participation and functional endurance were retained. Conclusion: Energetic led to sustainable improvements in social participation and functional endurance compared to usual care in patients with NMD and chronic fatigue. Clinicaltrials.gov identifier: NCT02208687. Classification of evidence: This study provides Class III evidence that a combination of aerobic training, energy conservation management, and relapse prevention improves social participation in patients with NMD and chronic fatigue.